2021
DOI: 10.3389/fmars.2020.614852
|View full text |Cite
|
Sign up to set email alerts
|

Regional Assessment of the Conservation Status of Snubfin Dolphins (Orcaella heinsohni) in the Kimberley Region, Western Australia

Abstract: Implementing conservation measures for data-limited species is a fundamental challenge for wildlife managers and policy-makers, and proves difficult for cryptic marine animals occurring in naturally low numbers across remote seascapes. There is currently scant information on the abundance and habitat preferences of Australian snubfin dolphins (Orcaella heinsohni) throughout much of their geographical range, and especially within the Kimberley region of northern Western Australia. Such knowledge gaps curtail ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 185 publications
(275 reference statements)
1
11
0
Order By: Relevance
“…For example, the Joint Cetacean Protocol (Paxton et al, 2016) proposes, among other recommendations, that the data supplied on effort and sightings must be related by a common code (to ensure that each sighting can be linked to the relevant unit of effort), and both must be geographically and temporally referenced. Thus, even when protocols vary widely, there are approaches which can be used to integrate multiple data sources so as to be able to infer patterns and trends in cetacean distribution and abundance (e.g., Cheney et al, 2013;Virgili et al, 2019;Waggitt et al, 2020;Bouchet et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Joint Cetacean Protocol (Paxton et al, 2016) proposes, among other recommendations, that the data supplied on effort and sightings must be related by a common code (to ensure that each sighting can be linked to the relevant unit of effort), and both must be geographically and temporally referenced. Thus, even when protocols vary widely, there are approaches which can be used to integrate multiple data sources so as to be able to infer patterns and trends in cetacean distribution and abundance (e.g., Cheney et al, 2013;Virgili et al, 2019;Waggitt et al, 2020;Bouchet et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to be especially true for resident populations, like that of the bottlenose dolphin (Bailey et al, 2013). Thirdly, despite increasing use of citizen science data on cetacean distribution and abundance (Bouchet et al, 2021), there is some skepticism about the use of such data in statutory population status assessments, due to perceived quality control issues such as the use of observers with various levels of training, possible misidentifications, and unconscious bias in effort toward times and locations with high cetacean occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The Australian snubfin dolphin (Orcaella heinsohni, hereafter, snubfin dolphin) was described as a separate species in 2005 and is endemic to the tropical waters of northern Australia and southern New Guinea (Beasley et al, 2005). Snubfin dolphins are typically found in shallow coastal waters (<20 m) and usually in proximity (<15 km) to freshwater inputs (Parra et al, 2002(Parra et al, , 2006bParra, 2006;Bouchet et al, 2021). Due to small population sizes and ongoing cumulative impacts across their coastal habitat, snubfin dolphins were assigned a conservation status of Vulnerable to extinction by the International Union for Conservation of Nature (IUCN) (Parra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to small population sizes and ongoing cumulative impacts across their coastal habitat, snubfin dolphins were assigned a conservation status of Vulnerable to extinction by the International Union for Conservation of Nature (IUCN) (Parra et al, 2017). Previous research suggests they are discontinuously distributed across their range as small local populations of 50-200 individuals (Parra et al, 2006a;Palmer et al, 2014b;Brown et al, 2016;Brooks et al, 2017;Bouchet et al, 2021) that exhibit site fidelity (Parra, 2006;Brown et al, 2016), and limited gene flow between populations (Brown et al, 2014b(Brown et al, , 2017. A recent study by Bouchet et al (2021) found that snubfin dolphins occupy a relatively small area within their distribution in the Kimberley, further highlighting the limited range and vulnerability of the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation